(3TQM OjhGf bjS Hf GdNWjes - (3CHi SYjO GdMSf Hf GdMSjfj Hf YHjO Gddg GdScQis; (3bjS Hf GdNWje Hf YOj GdChSj, CHh jRjO,fMh (B2 (3b g`s ((3YHO GdHGbi HQSe GdCejQ ejRQG eMehO NGf s)
(3ChdgG (B:s
(3Cfi SQjJ hcfJ ZjQ SQhH hJbQH GdCMdGe ZjQ bQjH s
(3BNQgG (B:s
(3hEfj dCYJGe GdQLGd HNdJi Chdi GdQCi ai GdCMOGK Mjf JMjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3HBNQgG JYbjHIs
(3hGdCHjGJ GdSJg GdCNjQg ZjQ eTQhMI hcCfgG de JcJed fSGNIs
(3bUGFO efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs